2006
DOI: 10.1103/physrevb.73.045109
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-selective insulator-metal transition inV2O3under external pressure

Abstract: We present a detailed account of the physics of Vanadium sesquioxide (V2O3), a benchmark system for studying correlation induced metal-insulator transition(s). Based on a detailed perusal of a wide range of experimental data, we stress the importance of multi-orbital Coulomb interactions in concert with first-principles LDA bandstructure for a consistent understanding of the PI-PM MIT under pressure. Using LDA+DMFT, we show how the MIT is of the orbital selective type, driven by large changes in dynamical spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 54 publications
2
46
0
Order By: Relevance
“…9,10) It is suggested that a Mott transition in some of relevant orbitals, i.e., an orbital selective Mott transition (OSMT), 11) is induced by the chemical substitution of Ca ions and also by the change in temperatures, where the heavy metallic state is realized. Furthermore, the pressure-induced OSMT is also suggested in the vanadium oxide V 2 O 3 , 12) which stimulates further theoretical and experimental 35,36) investigations on the effect of electron correlations in the system with orbital degeneracy.…”
Section: Introductionmentioning
confidence: 63%
“…9,10) It is suggested that a Mott transition in some of relevant orbitals, i.e., an orbital selective Mott transition (OSMT), 11) is induced by the chemical substitution of Ca ions and also by the change in temperatures, where the heavy metallic state is realized. Furthermore, the pressure-induced OSMT is also suggested in the vanadium oxide V 2 O 3 , 12) which stimulates further theoretical and experimental 35,36) investigations on the effect of electron correlations in the system with orbital degeneracy.…”
Section: Introductionmentioning
confidence: 63%
“…The features are well understood as follows. In a multiband situation, Δ acts like an external “Zeeman” field 39, 43 in the orbital sector. The insulator-metal transition is characterized by a sudden jump in the renormalized δ z , and in the p x and p y populations as a consequence, suggesting that anisotropic structural (and volume) changes will accompany the orbital-selective Mott transtion.…”
Section: Resultsmentioning
confidence: 99%
“…shows a first order metal-insulator transition at about 150-160 K, with an accompanying several-order decrease in specific resistivity and changes in crystallographic symmetry, lattice constants and spin ordering [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The doping of a small amount of Al, Cr or W, Ti can shift the transition temperature to high or low region [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%